2012
DOI: 10.1073/pnas.1204615109
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal pathogenicity island interference with helper phage reproduction is a paradigm of molecular parasitism

Abstract: Staphylococcal pathogenicity islands (SaPIs) carry superantigen and resistance genes and are extremely widespread in Staphylococcus aureus and in other Gram-positive bacteria. SaPIs represent a major source of intrageneric horizontal gene transfer and a stealth conduit for intergeneric gene transfer; they are phage satellites that exploit the life cycle of their temperate helper phages with elegant precision to enable their rapid replication and promiscuous spread. SaPIs also interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 32 publications
1
135
0
Order By: Relevance
“…Although in the cos phages (a) the TerL produces a second specific cut in the same cos site, generating unit-length encapsidated molecules, in the pac phages (b) the TerL generates a second cut in a sequence-independent manner only when the propcapsid reaches its capacity. generalized transduction is extremely rare, some mobile genetic elements [30][31][32] have made use of the impressive capabilities of phage particles to transfer DNA both intragenerically and inter-generically [33,34] and have developed elegant strategies to hijack the phage machinery to use for their own benefit [35 ]. The best-characterised elements are the S. aureus pathogenicity islands (SaPIs), which are mobile genetic elements that carry and disseminate superantigen genes, such as toxic shock toxin and enterotoxin B. SaPIs are the prototypical members of the 174 Host-microbe interactions: bacteria …”
Section: Hijacking the Hijackersmentioning
confidence: 99%
“…Although in the cos phages (a) the TerL produces a second specific cut in the same cos site, generating unit-length encapsidated molecules, in the pac phages (b) the TerL generates a second cut in a sequence-independent manner only when the propcapsid reaches its capacity. generalized transduction is extremely rare, some mobile genetic elements [30][31][32] have made use of the impressive capabilities of phage particles to transfer DNA both intragenerically and inter-generically [33,34] and have developed elegant strategies to hijack the phage machinery to use for their own benefit [35 ]. The best-characterised elements are the S. aureus pathogenicity islands (SaPIs), which are mobile genetic elements that carry and disseminate superantigen genes, such as toxic shock toxin and enterotoxin B. SaPIs are the prototypical members of the 174 Host-microbe interactions: bacteria …”
Section: Hijacking the Hijackersmentioning
confidence: 99%
“…In studies of SaPI interference with helper phage 80 (of the international typing set, a member of the famous 80/81 pair) (8), which is related to but is distinctly different from the more extensively studied 80α, we observed that SaPI2, the major cause of menstrual toxic shock, inhibits phage 80 reproduction more stringently than do other SaPIs, and preliminary results suggested that SaPI2 uses a third interference mechanism (7). In this report we characterize this third interference mechanism used by SaPI2 against phage 80 and other related phages but not against phage 80α.…”
mentioning
confidence: 99%
“…The SaPI life cycle is initiated only when the life cycle of a helper phage is in progress; SaPI particle production, however, is not quite able to keep up with helper phage maturation rate, and, perhaps to gain an advantage, SaPIs interfere with the reproduction of their helper phages (7). Thus far, two distinctly different SaPI-coded interference mechanisms have been identified, namely the capsid morphogenesis genes cpmA and B, which cause the formation of small capsids commensurate with the SaPI genome, and the phage packaging inhibition gene ppi, which blocks phage terminase small subunit (TerS P ), favoring the packaging of SaPI DNA.…”
mentioning
confidence: 99%
“…Previously characterized SaPIs and their helper phages use the pac mechanism for DNA encapsidation and encode small terminase subunit (TerS) homologs which complex with the phage-coded large terminase subunit and thus determine SaPI packaging specificity. This process is aided by a SaPI-coded protein, Ppi, which complexes with the phage TerS, blocking its function (1). Many of the SaPIs also encode a capsid morphogenesis module consisting of two proteins, CpmA and -B, which cause the formation of small procapsids that match the smaller size of the SaPI genome (2).…”
mentioning
confidence: 99%